Evangelicals and presidential politics: from Jimmy Carter to Donald Trump - Moore, Andrew S. (Louisiana State University Press, 2021)
Introduction : Jimmy Carter, the "Year of the Evangelicals," and the religious right / Andrew S. Moore -- Seeing red : evangelical and fundamentalist anticommunism and political engagement / Randall J. Stephens -- Full circle : the religious right from Bob Jones to Donald Trump / Randall Balmer -- An evangelical Black Panther : the politics of race and the conversion of Eldridge Cleaver / Dan Wells -- Building bridges and a broad-based movement : outreach to evangelicals and right-to-life strategy, 1972-1980 / Allison Vander Broek -- Evangelicals and abortion : the 1976 presidential election and evangelical pro-life partisanship / Daniel K. Williams -- Dwelling in the shelter of the most high : Ronald Reagan and the religious right / J. Brooks Flippen -- End of a life cycle : the decline and fall of southern evangelical political authenticity / Jeff Frederick -- A question of emphasis? : evangelicals, Trump, and the election of 2016 / R. Ward Holder -- Framing faith during the 2016 election : journalistic coverage of the Trump campaign and the myth of evangelical schism / Hannah Dick.